Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (GSP (Series), 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 86 peer-reviewed papers on geotechnical materials, modeling, and testing. Topics include: computational geotechnics; numerical modeling and analysis techniques; pavement subgrades and foundations; rock mechanics; soil properties and modeling; and unsaturated soils. GSP 310 will be of interest to practitioners and researchers in all areas of geotechnical engineering.